Polycationic structure directing agent and nano-sheet Beta molecular sieve and their preparation and application

By using the Jiyang ion structure guidance preparation to prepare nano -type BETA molecular sieves, the existing BETA molecular sieve spreads the problem of slow diffusion and structural damage in catalytic reactions, and achieves high -level multi -level tract structure synthesis and catalytic performance improvement.

CN118812372BActive Publication Date: 2025-01-28EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411259396.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-28
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

In the catalytic reaction, the existing beta molecular sieve has slow diffusion of micropores, resulting in a decrease in catalyst utilization, increased side reactions and reduced selectivity. At the same time, the multi-stage pore Beta molecular sieve with nanosponge or spherical structures is prone to damage the crystal structure during the synthesis process and Active site.

Method used

Adopt the concentration -oriented agent of Jiyang ion, and use nuclear replacement polymerization reactions and ion exchange technology to prepare nano -sliced ​​Beta molecular sieves with multi -level pores. This guide agent has a structural -oriented cationic center and a nail -based chain structure, which can regulate the connectivity of the medium degree and micropores and the metors, and synthesize a nano -shell -shaped BETA molecular sieve with a higher surface area and multi -level hole structure.

Benefits of technology

The efficient preparation of nano -sheet BETA molecular sieve is achieved, its diffusion performance is improved, the side reaction is reduced, and more reaction active sites are exposed on the surface, which enhances its performance as an adsorbent or catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812372B_ABST
    Figure CN118812372B_ABST
Patent Text Reader

Abstract

The present invention provides a polycationic structure directing agent and a nano-sheet Beta molecular sieve and preparation and application thereof, and relates to the technical field of molecular sieves. The polycationic structure directing agent provided by the present invention is a quaternary ammonium cationic polymer with a long-chain structure. The present invention mixes a silicon source, an aluminum source, an alkali source, the polycationic structure directing agent and water for hydrothermal crystallization, and roasts the obtained crystallized product to obtain a nano-sheet Beta molecular sieve. The present invention uses the polycationic structure directing agent to prepare the Beta molecular sieve into aluminosilicate nanosheets for the first time, which have multi-level pores, high specific surface area, abundant mesopores and adjustable acid density, and the diffusion path of the nanosheet is short, which can improve the diffusion performance, reduce side reactions, and expose more reactive sites on the surface. The nano-sheet Beta molecular sieve prepared by the present invention has excellent performance as an adsorbent or a catalyst for organic compound conversion, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieves, and in particular to a polycationic structure directing agent and a nano-sheet Beta molecular sieve, and preparation and application thereof. Background Art

[0002] Molecular sieves are microporous aluminosilicate crystals whose skeleton structure is formed by TO4 (T = Si, Al or P, etc.) tetrahedrons sharing O atoms. This structure gives them good ion exchange, (water) thermal stability, strong acidity, and unique molecular selective adsorption and shape-selective catalytic properties. Therefore, molecular sieves are widely used as ion exchangers, adsorbents and catalysts in the fields of washing industry, gas separation and purification, petroleum processing, coal chemical industry and fine chemical industry. In catalytic reactions, the diffusion and mass transfer of molecules in the micropores of molecular sieves are slow, which can easily lead to problems such as reduced catalyst utilization, easy side reactions and reduced selectivity, and easy carbon deposition and deactivation of catalysts. Nanosheet molecular sieves can solve a series of problems caused by the above-mentioned mass transfer difficulties and poor accessibility of acid sites due to their larger specific surface area, shorter pores and more acid sites accessible to macromolecules.

[0003] Beta molecular sieve is a The three-dimensional 12-membered ring macroporous molecular sieve with BEA topological structure has excellent hydrothermal stability, adjustable acidity and regular pore size. It is one of the zeolite catalysts with important industrial application value and is widely used in energy chemical industry, petrochemical industry, environmental protection and biomass conversion. In the conventional Beta molecular sieve synthesis method, tetraethylammonium hydroxide (TEAOH) is usually used as a structure directing agent. The obtained molecular sieve has a micron size and is easily affected by slow micropore diffusion in catalytic applications. The catalyst selectivity and anti-carbon deposition performance need to be improved. Although multi-level structure Beta molecular sieves can be prepared by post-treatment methods such as acid and alkaline, their crystal structure and active sites are usually damaged, resulting in partial collapse of the skeleton, reduced acid strength and insufficient hydrothermal stability. By adding pore-forming agents such as surfactants during the synthesis process, mesopores or macropores can be constructed on the basis of microporous molecular sieves. For example, Ryoo et al. [HS Shin et al., Appl. Catal. A-Gen , 2017, 537, 24-32.] Using supramolecular surfactants with polyammonium groups [C 22 H 45 -N + (CH3)2-C6H 12 -N + (CH3)2-CH2-(C6H4)-CH2-N + (CH3)2-C6H 12 -N +(CH3)2-CH2-(C6H4)-CH2-N + (CH3)2-C6H 12 -N + (CH3)2-C 22 H 45 ](Br - )2(Cl - )4(abbreviated as C 22 N6) as a bifunctional structure-directing agent to synthesize hierarchical nano-Beta molecular sieves; Yao et al. [Zhang, XF et al., Microporous Mesoporous Mater., 2018, 272, 202-208.] Structure-directing agents N(CH3)2-C6H obtained by cleaving the hydrophobic alkyl tail from conventional surfactant molecules 12 -N(CH + 3)2-CH2-(p-C6H4)-CH2-N(CH + 3) 2-C6H 12 -N(CH3)2[Cl - ]2 (abbreviated as N2-p-N2), successfully synthesized Beta molecular sieve with intracrystalline mesopores; Xiao et al. [Zhu J., J. Am. Chem. Soc ., 2014, 136:2503-2510.] Hierarchical single-crystalline Beta molecular sieves were synthesized using non-surfactant type polydiallyldimethylammonium chloride (PDADMA) structure-directing agent.

[0004] Although the above technology can obtain Beta molecular sieves with multi-level pore structures, the obtained Beta molecular sieves are nano-sponge-like or spherical, all of which are aggregated nanoparticles. There is no report on the synthesis of nano-sheet Beta molecular sieves. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a polycationic structure directing agent and a nano-sheet Beta molecular sieve and their preparation and application. The polycationic structure directing agent provided by the present invention can be used to prepare a nano-sheet Beta molecular sieve with multi-level pores.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a polycationic structure directing agent having a structure shown in Formula I or Formula II:

[0008] Formula I,

[0009] Formula II;

[0010] In the structure represented by Formula I or Formula II, n is an integer of 3 to 10.

[0011] The present invention provides a method for preparing the polycationic structure directing agent described in the above technical solution. When the polycationic structure directing agent has a structure shown in Formula I, the method comprises the following steps:

[0012] N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,5-dibromopentane and an organic solvent are mixed to carry out a nucleophilic substitution polymerization reaction to obtain a polycationic structure directing agent with a structure shown in formula I;

[0013] When the polycationic structure directing agent has a structure shown in Formula II, the method comprises the following steps:

[0014] The polycationic structure directing agent with the structure shown in formula I is subjected to ion exchange through a strongly basic anion exchange resin to obtain a polycationic structure directing agent with the structure shown in formula II.

[0015] The present invention provides a method for preparing a nano-flaky Beta molecular sieve, comprising the following steps:

[0016] A silicon source, an aluminum source, an alkali source, a structure directing agent and water are mixed for hydrothermal crystallization to obtain a crystallized product; the structure directing agent is the polycationic structure directing agent described in the above technical solution, and the alkali source is an alkali metal hydroxide; the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali source is calculated as an alkali metal element, and the structure directing agent is calculated as a structural unit, and the molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and the water is 1:(0.016-0.042):(0.05-0.20):(0.10-0.50):(10-100);

[0017] The crystallized product is calcined to obtain the nano-sheet-shaped Beta molecular sieve.

[0018] Preferably, the silicon source includes one or more of tetraethyl orthosilicate, sodium silicate, fumed silica, silica sol and white carbon black; the aluminum source includes one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium aluminate, pseudo-boehmite and aluminum isopropoxide; the alkali source includes one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide; the temperature of the hydrothermal crystallization is 110~190°C, and the time is 5~14 days.

[0019] Preferably, after the calcination, the obtained molecular sieve is subjected to ammonium exchange and secondary calcination in sequence to obtain a hydrogen-type nano-sheet Beta molecular sieve.

[0020] The present invention provides a nano-sheet Beta molecular sieve prepared by the preparation method described in the above technical solution. The nano-sheet Beta molecular sieve has a spherical structure formed by assembling nanosheets, and the nano-sheet Beta molecular sieve has micropores and mesopores.

[0021] Preferably, the thickness of the nanosheets in the spherical structure formed by the assembly of the nanosheets is 5-10 nm, the length is 110-200 nm, and the sphere diameter of the spherical structure is 500-1000 nm; the total specific surface area of ​​the nanosheet-like Beta molecular sieve is ≥600 m 2 / g, external specific surface area ≥300m 2 / g, total pore volume ≥ 0.90cm 3 / g, micropore volume ≥ 0.10cm 3 / g.

[0022] Preferably, the total acid content of the nano-sheet Beta molecular sieve is ≥500 μmol / g, and the strong acid content is ≥200 μmol / g.

[0023] The present invention provides a molecular sieve composition, comprising a Beta molecular sieve and a binder, wherein the Beta molecular sieve is the nano-sheet Beta molecular sieve described in the above technical solution.

[0024] The present invention provides the use of the nano-sheet Beta molecular sieve described in the above technical solution or the molecular sieve composition described in the above technical solution as an adsorbent or a catalyst for organic compound conversion.

[0025] The present invention provides a polycation structure directing agent having a structure shown in Formula I or Formula II. In the present invention, the polycation structure directing agent has a structure-directed cation center and a methylene chain structure, which can simultaneously direct the generation of microporous molecular sieves and generate auxiliary mesopores, and can regulate the mesoporosity and the connectivity between micropores and mesopores by controlling the length of the methylene chain; on the other hand, the higher positive charge density of the polycation in the polycation structure directing agent enables it to balance the negative charge on the Al position on the aluminum-rich molecular sieve framework, and is suitable for synthesizing Beta molecular sieves with a low silicon-aluminum ratio; moreover, the molecular size of the polycation structure directing agent is relatively large, and it is located in the pores to form nanosheets with a size similar to that of the polycation, and the mutual interaction between the polycations can prevent the continued growth of crystals, thereby synthesizing nanosheet-shaped Beta molecular sieves.

[0026] The present invention provides a method for preparing nano-sheet Beta molecular sieves, comprising the following steps: mixing a silicon source, an aluminum source, an alkali source, a structure directing agent and water for hydrothermal crystallization to obtain a crystallized product, wherein the structure directing agent is the polycationic structure directing agent described in the above technical scheme; and calcining the crystallized product to obtain the nano-sheet Beta molecular sieve. The present invention uses the polycationic structure directing agent to successfully synthesize nano-sheet multi-level pore structure Beta molecular sieves with different silicon-aluminum ratios, which have a high specific surface area, abundant mesopores and adjustable acid density, and the diffusion path of the nanosheets is short, which can improve the diffusion performance, reduce side reactions, and expose more reactive sites on the surface, which is conducive to the reaction of macromolecules. The nano-sheet Beta molecular sieve prepared by the present invention has excellent performance as an adsorbent or a catalyst for the conversion of organic compounds and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the X-ray diffraction pattern of the sodium-type nano-sheet Beta molecular sieve sample prepared in Example 2;

[0028] Figure 2 The SEM images of the sodium-type nano-sheet Beta molecular sieve samples prepared in Example 2 at different scales (5 μm, 2 μm, 1 μm, 500 nm);

[0029] Figure 3 This is a nitrogen adsorption-desorption isotherm diagram of the sodium-type nano-sheet Beta molecular sieve sample prepared in Example 2;

[0030] Figure 4 This is the NH3-TPD diagram of the hydrogen-type nano-sheet Beta molecular sieve sample prepared in Example 2;

[0031] Figure 5 This is the X-ray diffraction pattern of the nano-flaky Beta molecular sieve sample prepared in Example 3;

[0032] Figure 6 The SEM images of the nano-sheet Beta molecular sieve samples prepared in Example 3 at different scales (5 μm, 2 μm, 1 μm, 500 nm);

[0033] Figure 7 This is the X-ray diffraction pattern of the nano-flaky Beta molecular sieve sample prepared in Example 4;

[0034] Figure 8 These are SEM images of the nano-flaky Beta molecular sieve samples prepared in Example 4 at different scales (5 μm, 2 μm, 1 μm, 500 nm). DETAILED DESCRIPTION

[0035] The present invention provides a polycationic structure directing agent having a structure shown in Formula I or Formula II:

[0036] Formula I,

[0037] Formula II;

[0038] In the structure represented by Formula I or Formula II, n is an integer of 3 to 10.

[0039] In the present invention, the n is preferably 4-5.

[0040] The structure directing agent (SDA) provided by the present invention is a quaternary ammonium cationic polymer with a long chain structure. In the present invention, the chemical formula of the polycationic structure directing agent having the structure shown in formula I is [-N + (CH3)2-(CH2)5-N + (CH3)2-(CH2)6-] n [Br – ] 2n (Abbreviated as [Me4-5-6-Br2] n ), the chemical formula of the polycationic structure-directing agent having the structure shown in Formula II is [-N + (CH3)2-(CH2)5-N + (CH3)2-(CH2)6-] n [OH – ] 2n (Abbreviated as [Me4-5-6-(OH)2] n ).

[0041] The present invention provides a method for preparing the polycationic structure directing agent described in the above technical solution. When the polycationic structure directing agent has a structure shown in Formula I, the method comprises the following steps:

[0042] N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,5-dibromopentane and an organic solvent are mixed to carry out a nucleophilic substitution polymerization reaction to obtain a polycationic structure directing agent with a structure shown in formula I;

[0043] When the polycationic structure directing agent has a structure shown in Formula II, the method comprises the following steps:

[0044] The polycationic structure directing agent with the structure shown in formula I is subjected to ion exchange through a strongly basic anion exchange resin to obtain a polycationic structure directing agent with the structure shown in formula II.

[0045] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0046] When the polycationic structure directing agent has the structure shown in Formula I, the present invention mixes N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,5-dibromopentane and an organic solvent to carry out a nucleophilic substitution polymerization reaction to obtain a polycationic structure directing agent with the structure shown in Formula I.

[0047] In the present invention, the molar ratio of the N,N,N',N'-tetramethyl-1,6-hexanediamine to 1,5-dibromopentane is preferably 1:1. In the present invention, the organic solvent is preferably anhydrous methanol. The present invention has no special requirements for the amount of the organic solvent, as long as the raw material is dissolved and the reaction proceeds smoothly; in an embodiment of the present invention, the ratio of the total molar amount of the N,N,N',N'-tetramethyl-1,6-hexanediamine and 1,5-dibromopentane to the volume of the organic solvent is 0.20mol:100mL. The present invention preferably mixes the organic solvent and N,N,N',N'-tetramethyl-1,6-hexanediamine, and then slowly drops 1,5-dibromopentane into the resulting mixed solution.

[0048] In the present invention, the temperature of the nucleophilic substitution polymerization reaction is preferably 60-90°C, the time is preferably 24-96h, more preferably 36-48h, the nucleophilic substitution polymerization reaction is preferably carried out under reflux conditions, and the time of the nucleophilic substitution polymerization reaction is calculated from the completion of the dropwise addition of 1,5-dibromopentane. In the present invention, the reactions involved in the nucleophilic substitution polymerization reaction are as follows:

[0049] .

[0050] After the nucleophilic substitution polymerization reaction is completed, the present invention preferably performs rotary evaporation and washing in sequence on the obtained reaction solution to obtain a polycationic structure directing agent having a structure shown in Formula I. In the present invention, the role of the rotary evaporation is to remove the organic solvent; the washing agent used in the washing is preferably ethyl acetate, and the residual raw materials and solvent are removed by the washing to obtain a solid powdery polycationic structure directing agent.

[0051] When the polycationic structure-directing agent has a structure shown in Formula II, the present invention conducts ion exchange on the polycationic structure-directing agent with a structure shown in Formula I through a strongly basic anion exchange resin to obtain a polycationic structure-directing agent with a structure shown in Formula II.

[0052] In the present invention, the strong base anion exchange resin is preferably Amberlite IRA402 strong base anion exchange resin, specifically obtained by exchanging Amberlite IRA402 (chloride type) into OH type in NaOH solution, and the concentration of the NaOH solution is preferably 1 mol / L.

[0053] In the present invention, the specific operation of the ion exchange is preferably:

[0054] Dissolving the polycationic structure directing agent of the structure represented by Formula I in water, adding the strong basic anion exchange resin thereto, stirring and filtering in sequence, and collecting the filtrate;

[0055] The filtrate is subjected to rotary evaporation to obtain a polycationic structure directing agent having a structure shown in formula II.

[0056] In the present invention, the water is preferably deionized water, and the mass ratio of the polycationic structure directing agent of the structure shown in formula I to water is preferably 1:2~10, more preferably 1:5~6; the mass ratio of the polycationic structure directing agent of the structure shown in formula I to the strong basic anion exchange resin is preferably 1:1~5, more preferably 1:2.5~3.5. In the present invention, the stirring time (i.e., the ion exchange time) is preferably 8~24h, more preferably 10~12h. In the present invention, the filtrate is an aqueous solution of the polycationic structure directing agent of the structure shown in formula II. The present invention has no special requirements for the conditions of the rotary evaporation, and the water in the filtrate can be removed.

[0057] In the present invention, since ion exchange cannot guarantee a 100% exchange rate, the polycation structure directing agent obtained needs to be titrated with an acid after the rotary evaporation to determine the concentration of the OH-type polycation structure directing agent, and then added according to the amount of the OH-type polycation during the subsequent synthesis of the molecular sieve. In the present invention, the acid is preferably 0.1 mol / L hydrochloric acid.

[0058] The present invention provides a method for preparing a nano-flaky Beta molecular sieve, comprising the following steps:

[0059] A silicon source, an aluminum source, an alkali source, a structure directing agent and water are mixed for hydrothermal crystallization to obtain a crystallized product; the structure directing agent is the polycationic structure directing agent described in the above technical solution, and the alkali source is an alkali metal hydroxide; the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali source is calculated as an alkali metal element, and the structure directing agent is calculated as a structural unit, and the molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and the water is 1:(0.016-0.042):(0.05-0.20):(0.10-0.50):(10-100);

[0060] The crystallized product is calcined to obtain the nano-sheet-shaped Beta molecular sieve.

[0061] The present invention mixes a silicon source, an aluminum source, an alkali source, a structure directing agent and water for hydrothermal crystallization to obtain a crystallized product. In the present invention, the structure directing agent is the polycationic structure directing agent described in the above technical solution; the silicon source preferably includes one or more of tetraethyl orthosilicate, sodium silicate, fumed silica, silica sol and white carbon black; the aluminum source preferably includes one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium metaaluminate, pseudo-boehmite and aluminum isopropoxide; the alkali source is an alkali metal hydroxide, preferably including one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide; the water is preferably deionized water.

[0062] In the present invention, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali source is calculated as alkali metal elements, and the structure directing agent is calculated as structural units (i.e., Me4-5-6-Br2 or Me4-5-6-(OH)2). The molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and water is 1:(0.016-0.042):(0.05-0.20):(0.10-0.50):(10-100), preferably 1:(0.025-0.042):(0.10-0.20):(0.15-0.35):(20-60). In the present invention, the Si / Al ratio can be adjusted by adjusting the amount of the silicon source and the aluminum source, thereby achieving the acidity adjustment of the molecular sieve. The higher the Si / Al ratio, the lower the acid density.

[0063] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention has no special requirements for the stirring conditions, as long as the components are mixed evenly. The mixing can be carried out at room temperature, i.e., no additional heating or cooling is required.

[0064] In the present invention, the temperature of the hydrothermal crystallization is preferably 110-190°C, more preferably 160-180°C, and the time is preferably 5-14 days, more preferably 6-10 days, and further preferably 7-8 days. In the present invention, the hydrothermal crystallization is preferably carried out under static or dynamic conditions, the dynamic conditions are preferably stirring conditions, and the stirring rate is preferably 30 rpm.

[0065] After the hydrothermal crystallization is completed, the present invention sequentially performs solid-liquid separation, solid phase washing and drying on the obtained crystallization reaction liquid to obtain a crystallized product. The present invention has no special requirements for the method of solid-liquid separation, and methods well known to those skilled in the art can be used, such as filtration and suction filtration. In the present invention, the washing agent used for the washing is preferably deionized water and / or ethanol; the drying temperature is preferably 40~250℃, more preferably 60~150℃, further preferably 100℃, the time is preferably 8~30h, more preferably 10~20h, and the drying can be carried out under normal pressure or under reduced pressure.

[0066] After obtaining the crystallized product, the present invention calcines the crystallized product to obtain the nano-sheet Beta molecular sieve. In the present invention, the calcination temperature is preferably 300-800°C, more preferably 400-650°C, further preferably 500-550°C, and the time is preferably 1-10h, more preferably 3-6h; the calcination is preferably carried out in an oxygen-containing atmosphere, and the oxygen-containing atmosphere is preferably air or oxygen. The present invention removes the structure directing agent through the calcination to obtain an alkali metal Beta molecular sieve, specifically a sodium-type, potassium-type or lithium-type Beta molecular sieve.

[0067] After the calcination, the present invention also preferably performs ammonium exchange (or ammonium ion exchange) and secondary calcination on the obtained molecular sieve in sequence to obtain a hydrogen-type nano-sheet Beta molecular sieve. In the present invention, the ammonium exchange is preferably carried out in an ammonium salt solution, that is, the molecular sieve obtained after the calcination is immersed in an ammonium salt solution; the ammonium salt in the ammonium salt solution preferably includes one or more of ammonium chloride, ammonium nitrate, ammonium carbonate and ammonium sulfate, and the concentration of ammonium ions in the ammonium salt solution is preferably 0.1~1mol / L, more preferably 0.2~0.5mol / L; the solid-liquid mass ratio of the molecular sieve obtained after the calcination to the ammonium salt solution is preferably 1:5~1:20, more preferably 1:15~1:20. In the present invention, the temperature of the ammonium exchange is preferably 30~80°C, more preferably 55~65°C, the ammonium exchange is preferably carried out multiple times, the number of ammonium exchanges is preferably 1~3 times, and the time of a single ammonium exchange is preferably 1~8h, more preferably 3~5h. After the ammonium exchange is completed, the present invention preferably dries the obtained ammonium-type Beta molecular sieve, and the drying temperature is preferably 100° C. and the drying time is preferably 8 hours.

[0068] In the present invention, the secondary calcination temperature is preferably 500-600°C, more preferably 550°C, the time is preferably 3-8h, more preferably 4h, and the secondary calcination is preferably carried out in air. After the secondary calcination, a hydrogen-type nano-sheet Beta molecular sieve is obtained.

[0069] The invention provides a method for preparing nano-sheet Beta molecular sieves which is simple to operate and feasible. The method uses the polycationic structure directing agent for direct synthesis, and the synthesized molecular sieve has a wide silicon-aluminum ratio range and adjustable acid properties.

[0070] The present invention provides a nano-sheet Beta molecular sieve prepared by the preparation method described in the above technical solution. The nano-sheet Beta molecular sieve has a spherical structure formed by assembling nanosheets, and the nano-sheet Beta molecular sieve has micropores and mesopores.

[0071] In the present invention, the thickness of the nanosheets in the spherical structure (i.e., spherical aggregates) formed by the assembly of the nanosheets is preferably 5-10 nm, the length is preferably 110-200 nm, and the aspect ratio is preferably 11-40, more preferably 14-25; the sphere diameter of the spherical structure is preferably 500-1000 nm, more preferably 600-800 nm. In the present invention, the total specific surface area of ​​the nanosheet-like Beta molecular sieve is preferably ≥600m 2 / g, more preferably 600-700m 2 / g, the external specific surface area is preferably ≥300m 2 / g, more preferably 300-400m 2 / g, the total pore volume (micropores and mesopores) is preferably ≥ 0.90 cm 3 / g, more preferably 0.90~1.0cm 3 / g, the micropore volume is preferably ≥0.10cm 3 / g, more preferably 0.10~0.15cm 3 / g.

[0072] In the present invention, the total acid amount of the nano-sheet Beta molecular sieve is preferably ≥500 μmol / g, more preferably 500-1000 μmol / g, the strong acid amount is preferably ≥200 μmol / g, more preferably 200-400 μmol / g, and the proportion of the strong acid amount to the total acid amount is preferably ≥40%, more preferably 40-60%.

[0073] In the present invention, the silicon-aluminum molar ratio of the nano-sheet Beta molecular sieve is preferably 12-30 (ie, the SiO2 / Al2O3 molar ratio is 24-60).

[0074] The nanosheet-like Beta molecular sieve prepared by the present invention has a high specific surface area and a multi-level pore structure, and the acidity is adjustable, the mesopores and micropores are connected, and the accessibility is good (the nanosheet can expose more micropore openings, reducing the inaccessible acid sites in the longer micropore channels, and the presence of mesopores is conducive to the diffusion of substances into or out of the micropores), and has more accessible acid sites for the conversion reaction of macromolecular reactants. The present invention is the first to make Beta molecular sieve into aluminosilicate nanosheets with special crystal morphology and thickness reduced to less than 10nm. The diffusion path of the nanosheet is significantly shortened, which can improve the diffusion performance, reduce side reactions, and expose more reactive sites on the surface, which is conducive to the macromolecular reaction.

[0075] In the present invention, the nano-sheet Beta molecular sieve can be directly formed into different physical forms, such as powder, granular or molded product (such as strip, clover, etc.) through a molding process; the present invention has no special requirements for the molding process, and the molecular sieve molding process familiar to those skilled in the art can be used, such as rotation molding, compression molding, injection molding, etc.

[0076] The present invention provides a molecular sieve composition, comprising a Beta molecular sieve and a binder, wherein the Beta molecular sieve is the nano-sheet Beta molecular sieve described in the above technical solution.

[0077] In the present invention, the binder preferably includes one or more of aluminum sol, pseudo-boehmite, silica sol, silica-alumina sol and phosphate aluminum sol, and the mass of the binder is preferably 1-10% of the mass of the Beta molecular sieve.

[0078] In the present invention, the method for preparing the molecular sieve composition preferably comprises the following steps:

[0079] Mixing the Beta molecular sieve with a binder and a dispersion medium to obtain a mixture;

[0080] The mixed material is shaped to obtain the molecular sieve composition.

[0081] In the present invention, the type and amount of the binder are the same as those in the above technical solution. In the present invention, the dispersion medium is preferably water or acid, the acid is preferably nitric acid, phosphoric acid or hydrochloric acid, and the dispersion medium is selected according to the type of binder so that the binder is well dispersed; the mass of the dispersion medium is preferably 1.5 to 3 times the mass of the binder. In the present invention, the mixing is also preferably added with a pore-forming agent, the pore-forming agent is preferably starch, sodium carbonate, cellulose or polyvinyl alcohol, and the mass of the pore-forming agent is preferably 5 to 20% of the solid matter mass in the mixture. In the present invention, the mixing method is preferably stirring and mixing, so as to stir the components evenly. In the present invention, the molding method is preferably extrusion, tableting or spray drying (into a spherical shape), and the specific shape of the molding can be selected according to the needs.

[0082] In the present invention, the formed molecular sieve composition is easy to transport and separate and regenerate, has higher mechanical strength and is wear-resistant, and the aluminum binder can also provide a portion of acidity to play a synergistic catalytic role.

[0083] The present invention provides the use of the nano-sheet Beta molecular sieve described in the above technical solution or the molecular sieve composition described in the above technical solution as an adsorbent or a catalyst for organic compound conversion.

[0084] In the present invention, the nano-sheet-shaped Beta molecular sieve has a three-dimensional macroporous structure and high hydrothermal stability, and thus has a large adsorption capacity, water resistance and adsorption cycle stability. When the nano-sheet-shaped Beta molecular sieve or the molecular sieve composition is used as an adsorbent, it can adsorb heavy metals, dyes, and volatile organic compounds. In the present invention, the larger pore size of the nano-sheet-shaped Beta molecular sieve is conducive to the macromolecular reaction, and at the same time has strong acidity, a larger specific surface area and excellent hydrothermal stability. As a catalyst for the conversion of organic compounds, it can catalyze the cracking of alkanes to olefins, benzene alkylation, waste plastic cracking, and Friedel-Crafts acylation reactions.

[0085] In order to further illustrate the present invention, the polycationic structure directing agent and nano-sheet Beta molecular sieve provided by the present invention and their preparation and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.

[0086] In the embodiment, the structure of the nano-sheet Beta molecular sieve is determined by an X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) is measured by an X-ray powder diffractometer (model Panalytical X PERPRO, Cu Kα ray source (λ=1.5418 Å), nickel filter, 2θ scanning range 3~50 °, operating voltage 40kV, current 40mA, scanning rate 5° / min). Before the sample test, a scanning electron microscope (SEM, model S-4800II field emission scanning electron microscope) was used to observe the crystallization of the molecular sieve sample to confirm that the sample contained only one crystal, that is, the molecular sieve sample was pure phase, and then the XRD test was performed on this basis to ensure that there were no interference peaks of other crystals in the diffraction peaks in the XRD spectrum. The molecular sieve was observed under a scanning electron microscope at a magnification of 40,000 times. An observation field of view was randomly selected, and the average length of all nano-sheet crystals in the observation field of view was calculated. The operation was repeated 10 times in total, and the average of the sum of the 10 times was taken as the length of the nano-sheet crystal. The length and thickness of all crystals in the observation field of view were measured using the same method, and the operation was repeated 5 times.

[0087] In the embodiment, the micropore diameter, pore volume, specific surface area and external specific surface area of ​​the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by a physical adsorption instrument (Micromeretic ASAP2020M physical adsorption instrument), and then the BET equation and t The experimental conditions for Beta molecular sieve are: measurement temperature -196 ℃, and the molecular sieve is vacuum degassed at 350 ℃ for 4 hours before measurement.

[0088] In the embodiment, the molecular sieve is measured by an inductively coupled plasma atomic emission spectrometer (ICP) of model Varian 725-ES. The analysis sample is dissolved with hydrofluoric acid to obtain the content of the element in moles.

[0089] In the embodiment, the acid content of the molecular sieve is measured by NH3-TPD chemical adsorption-desorption curve using Altamira AMI-3300 instrument. Before the test, the sample is activated at 550°C for 1h, ammonia is adsorbed at 100°C for 20min, and then desorption is detected at 100-600°C. The peak area is quantified by quantitative ring pulse ammonia, and the peak is separated by Gaussian distribution, and the acid content corresponding to the desorption temperature above 300°C is identified as a strong acid.

[0090] Example 1

[0091] Preparation of polycationic structure directing agents:

[0092] 100 mL of anhydrous methanol and 17.2 g (0.10 mol) of N,N,N',N'-tetramethyl-1,6-hexanediamine were added to a 500 mL flask; 23.0 g (0.10 mol) of 1,5-dibromopentane was slowly added dropwise to the flask; the reaction was refluxed at 60°C for 48 h, and the methanol was removed by rotary evaporation after the reaction was completed. The residual raw materials and solvent were removed by washing with ethyl acetate, and the product was recrystallized into a white solid powder to obtain a polycationic structure directing agent [-N + (CH3)2-(CH2)5-N + (CH3)2-(CH2)6-] n [Br – ] 2n (shown in formula Ⅰ), denoted as [Me4-5-6-Br2] n , the average degree of polymerization n is 5.

[0093] 20.0 g [Me4-5-6-Br2] n Dissolve in 100.0g deionized water, add 50g Amberlite IRA402 strong base anion exchange resin (Amberlite IRA402 (chloride type) is exchanged into OH type in 1mol / L NaOH solution), stir for 12h, filter and collect the filtrate; evaporate the filtrate to remove water, titrate with 0.1mol / L hydrochloric acid to obtain the polycationic structure directing agent [-N + (CH3)2-(CH2)5-N + (CH3)2-(CH2)6-] n [OH – ] 2n (shown in formula II), denoted as [Me4-5-6-(OH)2] n .

[0094] Example 2

[0095] Preparation of Nano-Flake Beta Molecular Sieve:

[0096] 8.00g deionized water, 0.40g [Me4-5-6-Br2] n (SDA, prepared in Example 1), 0.06 g sodium aluminate (content 80 wt%), 0.14 g sodium hydroxide, 0.60 g white carbon black, and stirred at room temperature for 24 h to obtain a mixture. The final molar ratio of the mixture was: SiO2 / Al2O3=34, NaOH / SiO2=0.35, SDA / SiO2=0.10, H2O / SiO2=44, wherein SDA was calculated based on the structural unit Me4-5-6-(Br)2;

[0097] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 8 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. overnight, and calcined in air at 550° C. for 6 hours to obtain a sodium-type nano-sheet Beta molecular sieve sample.

[0098] Figure 1 This is the X-ray diffraction pattern of the sodium-type nano-sheet Beta molecular sieve sample prepared in Example 2, confirming that the sample is a Beta molecular sieve.

[0099] Figure 2 The following are SEM images of the sodium-type nano-sheet Beta molecular sieve samples prepared in Example 2 at different scales (5 μm, 2 μm, 1 μm, and 500 nm). Figure 2 It can be seen that the molecular sieve has an elliptical nanosheet morphology with a thickness of 5~10nm, a length of 110~200nm, a sphere diameter of 600~900nm, and an aspect ratio of 11~40.

[0100] The SiO2 / Al2O3 molar ratio of the molecular sieve was measured to be 30 by inductively coupled plasma atomic emission spectroscopy (ICP).

[0101] Figure 3 This is the nitrogen adsorption-desorption isotherm diagram of the sodium-type nano-sheet Beta molecular sieve sample prepared in Example 2. Figure 3 As shown, the total specific surface area of ​​the molecular sieve is 652m 2 / g, and the external specific surface area measured by BET method is 364m 2 / g; the total pore volume (micropores and mesopores) is 0.97cm 3 / g, micropore volume is 0.13cm 3 / g, and the micropore diameter is 0.67nm.

[0102] The sodium-type nano-sheet Beta molecular sieve prepared in Example 2 was subjected to ammonium ion exchange with 0.20 mol / L NH4NO3 solution (solid-liquid mass ratio 1:20) at 65°C for 3 h, followed by centrifugal washing. After repeating the ammonium ion exchange twice, the obtained sample was dried at 100°C for 8 h, and calcined in air at 550°C for 4 h to prepare the hydrogen-type nano-sheet Beta molecular sieve.

[0103] Figure 4 This is the NH3-TPD diagram of the prepared hydrogen-type nanosheet Beta molecular sieve sample. Figure 4 It was found that the total acid content of the hydrogen-type nano-sheet Beta molecular sieve sample was 557 μmol / g, the strong acid content was 278 μmol / g, and the strong acid content accounted for 50% of the total acid content.

[0104] Example 3

[0105] 32.00g deionized water, 1.60g [Me4-5-6-Br2] n (SDA, prepared in Example 1), 0.56 g of sodium hydroxide, 0.24 g of sodium aluminate (content 80 wt%), and 2.40 g of white carbon black were stirred at room temperature for 24 h to obtain a mixture, and the final molar ratio of the mixture was: SiO2 / Al2O3=34, NaOH / SiO2=0.35, SDA / SiO2=0.10, H2O / SiO2=44, wherein SDA was calculated as the structural unit Me4-5-6-(Br)2;

[0106] The mixture was placed in a stainless steel reactor and heated for crystallization at 180°C (30 rpm) for 8 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100°C for 8 hours, and calcined in air at 550°C for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0107] The X-ray diffraction pattern of the nano-sheet Beta molecular sieve sample prepared in Example 3 is as follows: Figure 5 As shown, it is Beta molecular sieve, and the SEM image of the sample is as follows Figure 6 As shown, it is an elliptical nanosheet morphology with a thickness of 8-10 nm, a length of 120-180 nm, a sphere diameter of 500-900 nm, and an aspect ratio of 12-23. The SiO2 / Al2O3 molar ratio of the molecular sieve is 31 as measured by inductively coupled plasma atomic emission spectroscopy (ICP).

[0108] Example 4

[0109] 9.28g deionized water, 0.32g [Me4-5-6-(OH)2] n(SDA, prepared in Example 1), 0.14 g of sodium hydroxide, 0.07 g of sodium aluminate (content 80 wt%), and 0.69 g of white carbon black were stirred at room temperature for 24 h to obtain a mixture, and the final molar ratio of the mixture was: SiO2 / Al2O3=34, NaOH / SiO2=0.3, SDA / SiO2=0.1, H2O / SiO2=44, wherein SDA was calculated based on the structural unit Me4-5-6-(OH)2;

[0110] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 8 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. overnight, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0111] The X-ray diffraction pattern of the nano-sheet Beta molecular sieve sample prepared in Example 4 is as follows: Figure 7 As shown, it is Beta molecular sieve, and the SEM image of the sample is as follows Figure 8 As shown, it is an elliptical nanosheet morphology with a thickness of 6-9 nm, a length of 140-200 nm, a sphere diameter of 500-600 nm, and an aspect ratio of 15-33. The SiO2 / Al2O3 molar ratio of the molecular sieve is 30 measured by inductively coupled plasma atomic emission spectroscopy (ICP).

[0112] Example 5

[0113] 7.72g deionized water, 0.27g [Me4-5-6-(OH)2] n (SDA, prepared in Example 1), 0.12 g of sodium hydroxide, 0.08 g of sodium aluminate (content 80 wt%), and 0.58 g of white carbon black were stirred at room temperature for 24 h to obtain a mixture, and the final molar ratio of the mixture was: SiO2 / Al2O3=24, NaOH / SiO2=0.3, SDA / SiO2=0.1, H2O / SiO2=44, wherein SDA was calculated based on the structural unit Me4-5-6-(OH)2;

[0114] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 8 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. for 8 hours, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0115] Example 6

[0116] 8.00g deionized water, 0.40g [Me4-5-6-Br2] n(SDA, prepared in Example 1), 0.14 g of sodium hydroxide, 0.07 g of sodium aluminate (content 80 wt%), and 0.60 g of white carbon black were stirred at room temperature for 24 h to obtain a mixture, and the final molar ratio of the mixture was: SiO2 / Al2O3=28, NaOH / SiO2=0.35, SDA / SiO2=0.10, H2O / SiO2=44, wherein SDA was calculated based on the structural unit Me4-5-6-(Br)2;

[0117] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 8 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. for 8 hours, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0118] Example 7

[0119] The synthesis steps and conditions are similar to those of Example 5, except that:

[0120] Silica sol (40% mass concentration) was used as the silicon source, and the molar ratio of the final mixture was: SiO2 / Al2O3=28, NaOH / SiO2=0.35, SDA / SiO2=0.10, H2O / SiO2=44, where SDA was calculated as the structural unit Me4-5-6-(OH)2;

[0121] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 7 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. overnight, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0122] Example 8

[0123] The synthesis steps and conditions are similar to those of Example 4, except that:

[0124] Fumed silica was used as the silicon source, and the molar ratio of the final mixture was: SiO2 / Al2O3=24, NaOH / SiO2=0.35, SDA / SiO2=0.10, H2O / SiO2=44, where SDA was calculated as the structural unit Me4-5-6-(OH)2;

[0125] The mixture was placed in a stainless steel reactor and heated for crystallization at 180° C. for 7 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. overnight, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0126] Example 9

[0127] The synthesis steps and conditions are similar to those of Example 4, except that:

[0128] Potassium hydroxide was used as the alkaline source, and the molar ratio of the final mixture was: SiO2 / Al2O3=24, KOH / SiO2=0.33, SDA / SiO2=0.10, H2O / SiO2=44, where SDA was calculated as the structural unit Me4-5-6-(OH)2;

[0129] The mixture was placed in a stainless steel reactor and heated for crystallization at 170° C. for 7 days. After the crystallization, the mixture was filtered, washed, dried in an oven at 100° C. overnight, and calcined in air at 550° C. for 6 hours to obtain a nano-sheet Beta molecular sieve sample.

[0130] Application Examples

[0131] The hydrogen-type nano-sheet Beta molecular sieve prepared in Example 2 was used as a catalyst for the n-heptane cracking reaction. The reaction conditions were: reaction temperature of 600°C, mass space velocity WHSV = 6 g 正庚烷 ·g 催化剂 -1 · h -1 , the reaction carrier gas was nitrogen, and the reaction time was 1h. Reaction results: the total yield of ethylene and propylene was 58%.

[0132] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing nano-flaky Beta molecular sieve, characterized in that: The following steps are involved: A silicon source, an aluminum source, an alkali source, a structure directing agent and water are mixed for hydrothermal crystallization to obtain a crystallized product; the structure directing agent is a polycationic structure directing agent, and the alkali source is an alkali metal hydroxide; the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali source is calculated as an alkali metal element, and the structure directing agent is calculated as a structural unit, and the molar ratio of the silicon source, the aluminum source, the structure directing agent, the alkali source and the water is 1:(0.016-0.042):(0.05-0.20):(0.10-0.50):(10-100); calcining the crystallized product to obtain the nano-sheet-shaped Beta molecular sieve; The polycationic structure directing agent has a structure shown in Formula I or Formula II: Formula I, Formula II; In the structure represented by Formula I or Formula II, n is an integer of 3 to 10.

2. The method for preparing nano-flaky Beta molecular sieve according to claim 1, characterized in that: When the polycationic structure directing agent has a structure as shown in Formula I, the preparation method of the polycationic structure directing agent comprises the following steps: N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,5-dibromopentane and an organic solvent are mixed to carry out a nucleophilic substitution polymerization reaction to obtain a polycationic structure directing agent with a structure shown in formula I; When the polycationic structure directing agent has a structure shown in Formula II, the preparation method of the polycationic structure directing agent comprises the following steps: The polycationic structure directing agent with the structure shown in formula I is subjected to ion exchange through a strongly basic anion exchange resin to obtain a polycationic structure directing agent with the structure shown in formula II.

3. The method for preparing nano-flaky Beta molecular sieve according to claim 1, characterized in that: The silicon source includes one or more of ethyl orthosilicate, sodium silicate, fumed silica, silica sol and white carbon black; the aluminum source includes one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium metaaluminate, pseudo-boehmite and aluminum isopropoxide; the alkali source includes one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide; the temperature of the hydrothermal crystallization is 110-190° C., and the time is 5-14 days.

4. The method for preparing nano-flaky Beta molecular sieve according to claim 1, characterized in that: After the calcination, the obtained molecular sieve is subjected to ammonium exchange and secondary calcination in sequence to obtain a hydrogen-type nano-sheet Beta molecular sieve.

5. The nano-flaky Beta molecular sieve prepared by the preparation method of the nano-flaky Beta molecular sieve according to any one of claims 1 to 4, wherein the nano-flaky Beta molecular sieve has a spherical structure formed by assembling nano-sheets, and the nano-flaky Beta molecular sieve has micropores and mesopores.

6. The nano-sheet Beta molecular sieve according to claim 5, characterized in that: The nanosheets in the spherical structure formed by assembling the nanosheets have a thickness of 5-10 nm, a length of 110-200 nm, and a spherical diameter of 500-1000 nm; the total specific surface area of ​​the nanosheet-like Beta molecular sieve is ≥600 m 2 / g, external specific surface area ≥300m 2 / g, total pore volume ≥ 0.90cm 3 / g, micropore volume ≥ 0.10cm 3 / g.

7. The nano-sheet-like Beta molecular sieve according to claim 5, characterized in that: The total acid content of the nano-sheet Beta molecular sieve is ≥500 μmol / g, and the strong acid content is ≥200 μmol / g.

8. A molecular sieve composition, characterized in that: The invention comprises a Beta molecular sieve and a binder, wherein the Beta molecular sieve is the nano-sheet-shaped Beta molecular sieve as claimed in any one of claims 5 to 7.

9. Use of the nano-sheet Beta molecular sieve according to any one of claims 5 to 7 or the molecular sieve composition according to claim 8 as an adsorbent or a catalyst for conversion of organic compounds.

Citation Information

Patent Citations

  • Preparation method of micro-mesoporous structure Beta molecular sieve

    CN106185972A

  • Composite material with high conductivity and high flexibility, ion exchange membrane and application thereof

    CN117285819A